On the Embedding of an Arc Into a Cubic Curves in a Finite Projective Plane of Order Five - AL-Seraji, Najm A. M.; AL-Humaidi, Raad I. K. (Iraqi Journal of Science, 2018)
The main aims of this research is to find the stabilizer groups of a cubic curves over a finite field of order , studying the properties of their groups and then constructing the arcs of degree which are embedding in a cubic curves of even size which are considering as the arcs of degree . Also drawing all these arcs.